Application of spectral gamma and magnetic susceptibility in a As bearing loessic aquifer, Argentina - Sierra, Leonardo (2018)
Application of Natural Gamma Spectroscopy (NGS) borehole logging and magnetic susceptibility (χ) on aquifer samples are compared with the identified mineralogy and trace elemental analyses. Acceptable correlation between ICP analyses (K and Th) and NGS signals has been found. However, some observed discrepancies on them could be related to the different exploratory volumes of each technique. Magnetic Susceptibility measurements present better correlations between the superparamagnetic signal (χdf) and As contents, probably linked to the pedogenetic origin of such particles.